Evaluation of social impact of traffic noice in Amman, Jordan - KHAIR JADAAN; HALA GAMMOH; RAMI AMMOURAH; ZAINA AI-NABULSI (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
Few road traffic studies were conducted in Jordan, but the issue is drawing an increasing attention due to its growing magnitude and various impacts as a result of the high increase in vehicular traffic. This study further investigates the issue with the aim of providing an understanding of its social impact on residents of Amman, the capital of Jordan. Traffic noise levels were measured at selected locations along urban arterials and a social survey was performed to examine the reactions and attitudes of the neighboring residents towards these levels of traffic noise. The survey included social characteristics of individuals, and their attitudes towards traffic noise, and how it impacted their daily activities. A predesigned questionnaire was used for this purpose which included questions to evaluate the awareness of respondents of the problem and its environmental and health impacts. The financial impact that residents perceive of noise and the need for attenuation measures were also addressed. The results of the study also revealed that the impact of traffic noise on people can cause annoyance while performing daily activities were 24% of respondents reported that they get annoyed by traffic while working, 49% while resting, 34% while talking to others, 31% while talking on the phone, 39% while reading, 38% while watching TV and 53% of respondents get annoyed while sleeping. The respondents have also pointed out the following effects of noise: twist in mood (53%), headache (36%), and difficulty in concentration (40%). About 57% of respondents think traffic noise reduces the value of their properties and a total of 31% are willing to sell their house at reduced cost. About 59% of respondents consider attenuation measures necessary, and in order to reduce the noise, about 54% of respondents were willing to pay for attenuation measures which reflects the public awareness of the issue magnitude. Keywords: traffic noise, noise level, survey, social impacts.